Clinical utility of a next generation sequencing panel assay for Marfan and Marfan‐like syndromes featuring aortopathy. (5th May 2015) - Wooderchak‐Donahue, Whitney; VanSant‐Webb, Chad; Tvrdik, Tatiana; Plant, Parker; Lewis, Tracey; Stocks, Jennifer; Raney, Joshua A.; Meyers, Lindsay; Berg, Alizabeth; Rope, Alan F.; Yetman, Anji T.; Bleyl, Steven B.; et al.
<x xml:space="preserve">Abstract</x> Aortopathy can be defined as aortic dilation, aneurysm, dissection, and tortuosity. Familial aortopathy may occur secondary to fibrillin‐1 (FBN1) mutations in the setting of Marfan syndrome, or may occur as a result of other genetic defects with different, but occasionally overlapping, phenotypes. Because of the phenotypic overlap and genetic heterogeneity of disorders featuring aortopathy, we developed a next generation sequencing (NGS) assay and comparative genomic hybridization (CGH) array to detect mutations in 10 genes that cause thoracic aortic aneurysms (TAAs). Here, we report on the clinical and molecular findings in 175 individuals submitted for aortopathy panel testing at ARUP laboratories. Ten genes associated with heritable aortopathies were targeted using hybridization capture prior to sequencing. NGS results were analyzed, and variants were confirmed using Sanger sequencing. Array CGH was used to detect copy‐number variation. Of 175 individuals, 18 had a pathogenic mutation and 32 had a variant of uncertain significance (VUS). Most pathogenic mutations (72%) were identified in FBN1. A novel large SMAD3 duplication and FBN1 deletion were identified. Over half who had TAAs or other aortic involvement tested negative for a mutation, suggesting that additional aortopathy genes exist. We anticipate that the clinical sensitivity of at least 10.3% will rise with VUS reclassification and as additional genes are identified and included in the panel. The aortopathy NGS panel aids in the timely molecular diagnosis of individuals with disorders featuring aortopathy and guides proper treatment. © 2015 Wiley Periodicals, Inc.